Predicting the phase diagram of two-dimensional colloidal systems with long-range interactions - Mejía Rosales, Sergio; Gil Villegas, Alejandro; Ivlev, Boris I.; Ruiz García, Jaime (American Chemical Society, 2006)
The phase diagram of a two-dimensional model system for colloidal particles at the air-water interface was determined using Monte Carlo computer simulations in the isothermic-isobaric ensemble. The micrometerrange binary colloidal interaction has been modeled by hard disklike particles interacting via a secondary minimum followed by a weaker longer-range repulsive maximum, both of the order of kBT. The repulsive part of the potential drives the clustering of particles at low densities and low temperatures. Pinned voids are formed at higher densities and intermediate values of the surface pressure. The analysis of isotherms, translational and orientational correlation functions as well as structure factor gives clear evidence of the presence of a melting first-order transition. However, the melting process can be also followed by a metastable route through a hexatic phase at low surface pressures and low temperatures, before crystalization occurs at higher surface pressure